The Role of Leading Subsectors on Provincial Own-Source Revenue in Eastern Indonesia with Archipelagic Characteristics in 2015–2023 - Ginting, Ronaldo Keristanta; Nasrudin (Jurnal Pajak dan Keuangan Negara (PKN), 2024)
To increase regional fiscal independence and achieve regional development goals in the Eastern Indonesia (KTI) in the era of fiscal decentralization, own-source revenue (PAD) is one source of regional revenue that is important to optimize based on regional economic potential. Thus, this research aims to analyze the leading subsectors and the influence on provincial PAD in KTI with archipelagic characteristics in 2015 – 2023. By overlaying location quotient and shift share analysis, eight leading subsectors in KTI with archipelagic characteristics were obtained. Next, the seven leading subsectors outside the public administration and defence, compulsory social security subsector analyzed by panel data regression with a fixed effect model, state that the five leading subsectors including crop and animal production, hunting and related service activities; fishing and aquaculture; other mining and quarrying; construction; and education have a significant effect, while the wholesale and retail trade and repair of motor vehicles and motorcycles and the air transport do not have a significant effect on the provincial PAD in KTI with archipelagic characteristics in 2015 - 2023. Therefore, the provincial government is expected to prioritize leading subsectors that have a significant positive influence to be developed in optimizing the provincial PAD in KTI with archipelagic characteristics.